THE INFLUENCE OF PERSON-JOB FIT TOWARD JOB SATISFACTION, ORGANIZATIONAL COMMITMENT, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Study on Civil Servants in Marine & Fisheries Agency and Provincial Inspectorate Agency in West Borneo) - admin, Muhammad Etsa Akbari B1024141013 (Jurnal Manajemen Update, 2021)
AbstractAn organization will have human resource management as the central factor which is can be useful to do, manage, and reach the vision and mission that already set by the organization. The quality of the employee is one of the key that can determine improvement of an organization. The success of development program that implemented by the government is depend on the quality and quantity of the human resources that the government have and the management of the human resource in the company can be review from the organizational behavior that happen in the organization. The purpose of this study is to analyze the impact of Person-Job Fit toward Job Satisfaction, Organizational Commitment, and Organizational Citizenship Behavior in Marine & Fisheries Agency and Provincial Inspectorate Agency in West Borneo. The sampling technique that used in this research is using the 10 times formative indicator. The data is evaluated by Structural Equation Model (SEM) and to analyze the data it is use SmartPLS 3.0 software application. The result of this research are: (1) Person-Job Fit is have significant impact on Job Satisfaction, (2) Person-Job Fit is have significant impact on Organizational Commitment, (3) Job Satisfaction is have significant impact on Organizational Commitment, (4) Person-Job Fit is not have significant impact toward Organizational Citizenship Behavior, (5) Job Satisfaction is have significant impact toward Organizational Citizenship Behavior, and (6) Organizational Commitment is not have significant impact toward Organizational Citizenship Behavior.Keywords : Â Â Â Â  Person-Job Fit, Job Satisfaction, Organizational Commitment, Organizational Citizenship BehaviorÂ ReferenceesÂ A.K.M. Tafzal HAQUE, M. A. (2019). Job Satisfaction and Citizenship Behavior: A Mediating Effect of Organizational Commitment. Organizacija Research Papers Volume 52.Abdillah, W., & Hartono, J. (2015). Partial Least Square (PLS): Alternatif Structural Equation Modelling (SEM) dalam Penelitian Bisnis. Yogyakarta: Penerbit Andi.Allen N. J, M. J. (1997). Commitment in the Workplace. London: Sage Publication.Angelo Kinicki, R. K. (2010). Organizational Behavior: Key Concepts, Skills & Best Practices (3rd ed.). New York: McGraw-Hill Ryerson.Azman Ismail, M. A. (2016). Effect of Job Satisfaction on Organizational Commitment. Management&Marketing Journal, 25.Chhabra, B. (2015). Person-Job Fit: Mediating Role of Job Satisfaction & Organizational Commitment. The Indian Journal of Industrial Relations, Vol. 50, No. 4.Cohen. (2003). Applied Multiple Regression/Correlation Analysis in the Behavioral Sciences (3rd ed.). Erlbaum.Dafler, F. (2013, April 23). Memahami dan Mempelajari SmartPLS. Dipetik October 17, 2020, dari feroniadafler.blogspot.co.id: http://feroniadafler.blogspot.co.id/2013/04/mempelajari-dan-memahami-smartpls.htmlDavid A. Kenny, R. M. (1986). The Moderator-Mediator Variable Distinction in Social Psychological Research: Conceptual, Strategic, and Statistical Considerations. Journal of Personality and Social Physchology, 51.Douglas A Lind, W. G. (2002). Basic Statistics for Business & Economics (4th ed.). (M. Hill, Penyunt.)Dr. Garima Mathur, M. S. (2015). Organizational Commitment and Job Satisfaction: A Study of Manufacturing Sector. Tirpude's National Journal of Business and Research.Fatma Nur Iplik, K. C. (2011). The Simultaneous Effects of Person-Organization and Person-Job Fit on Turkish Hotel Managers. International Journal of Contemporary Hospitality Management, 1.Ghozali, P. D. (2006). Structural Equation Modeling Metode Alternatif Dengan PLS. Badan Penerbit Universitas Diponegoro.Goh Ee Leng, M. L. (2016). Person-Job Fit, Personality, Organizational Commitment, and Intention to Stay Among Employees in Marketing Department. Jurnal Psikologi Malaysia.GUNAY, D. G. (2018). Relationship Between Job Satisfaction, Organizational Citizenship Behavior, and Employee Performance: Sample of Edirne Financial Office Employees in Turkey. American International Journal of Contemporary Research.Hadini, M. A. (2018). The Influence of Person Job Fit and Person Organization Fit toward Organizational Citizenship Behavior and Employee Performance of Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin. Journal of Research and Management Vol.2 No.2.Helisia Margahana, S. H. (2018). The Effect of Job Motivation and Job satisfaction Toward OCB and Its Impact on Job Performance of Paramedical Country Health Centers in the City of Bandar Lampung. Journal of Resource Development and Management.Ikonne, C. N. (2015). Job Satisfaction and Organizational Citizenship Behavior of Library Personnel in Selected Nigerian Universities. International Journal of Science and Research.Ilyas, S. (2013). Combined effects of person job fit and organization commitment on attitudinal outcomes such as job satisfaction and intention to quit. The 2013 WEI International Academic Conference Proceedings.Iqbal, M. T. (2012). The Impact of Person-Job Fit and its Subsequent Impact on Employees Performance. Mediteranian Journal of Social Sciences.Jacob Cohen, P. C. (2003). Applied Multiple Regression/Correlation Analysis in the Behavioral Sciences (3rd ed.). Erlbaum.James L. Gibson, J. M. (2013). Organization: Behavior, Structure, Process (8th ed.). California: McGraw-Hill Education.Jason A. Colquitt, J. A. (2015). Organizational Behavior: Improving Performance and Commitment in the Workplace (4th ed.). New York: McGraw Hill Education.John R. Schermerhorn Jr., R. N.-B. (2012). Organizational Behavior (12th ed.). United State: John Wiley & Sons Inc.Kabir, Z. F. (2018). Effect of Job Satisfaction and Organizational Commitment on OCB: Study on Private Banks in Bangladesh. World Journal of Social Sciences Vol.8 No.2.Khaleh, L. A. (2016). The relationship between organizational commitment components and organizational citizenship behavior in nursing staff. International Journal of Medical Research & Health Science.KILIC, E. (2013). The Relationship Among Organizational Commitment and Organizational Citizenship Behavior â€“A Research Study On Call Center Employees. â€œIS, GUCâ€ Industrial Relations And Human Resources Journal.Kristof, A. L. (2013). Person Organization Fit: An Integrative Review of its Conceptualization, Measurement and Implication (1st ed.). Wiley Blackwell.Kuncoro, M. (2009). Metode Riset untuk Bisnis & Ekonomi (3rd ed.). Penerbit Erlangga.Lind, D. A. (2002). Basic Statistics for Business & Economics (4th ed.). (M. Hill, Penyunt.)Luthans, F. (2005). Organizational Behavior (10th ed.). Indonesia: Penerbit Andi.Luthans, F. (2011). Organizational Behavior: An Evidence-Based Approach (12th ed.). North Americs: McGraw Hill.Margahana, H. (2018). The Effect of Job Motivation and Job Satisfaction Toward Organizational Citizenship Behavior (OCB) and Its Impact on Job Performance of Paramedical Community Health Centers in the City of Bandar Lampung. Journal of Resources Development and Management, 46.Maria Sayaz-Ortiz, E. R. (2014). Relationship Between Organizational Commitment and Organizational Citizenship Behavior in A Sample Of Private Bank Employees. International Journal of Sociology and Social Policy.Michael Asiedu, J. O. (2014). Organizational Commitment and Citizenship Behavior: Tools to Improve Employee Performance; An Internal Marketing Approach. European Scientific Journal.Mudrajad Kuncoro, P. (2009). Metode Riset untuk Bisnis & Ekonomi (3rd ed.). Penerbit Erlangga.Muh.Akmal Ibrahim, A. A. (2013). Relationship between Organizational Commitment and OCB At Government-Owned Corporation Companies. Journal of Public Administration and Governance.Noor, J. (2015). Metodologi Penelitian: Skripsi, Tesis, Disertasi, dan Karya Ilmiah (5th ed.). Jakarta: Prenadamedia Group.Nwibere, B. (2014). Interactive Relationship Between Job Involvement, Job Satisfaction, OCB, and Organizational Commitment in Nigerian Universities. International Journal of Management and Sustainability.Philip M. Podsakoff, S. B. (2000). Organizational Citizenship Behavior: A Critical Review of the Theoritical and Empirical Literature and Suggestions for Future Research. Journal of Management No.26 no.3 , 516-525.Riadi, D. E. (2016). Statistika Penelitian (Analisis Manual dan IBM SPSS). Penerbit Andi.Robbins, S. P. (2013). Organizational Behavior (15th ed.). New Jersey: Pearson.S. Suwanti, U. U. (2018). Person-Organization Fit, Person-Job Fit, and Innovative Work Behavior: The Role of Organiozational Citizenship Behavior. International Journal of Economics and Business Administration.Sekaran. (2013). Research Method for Business: A Skill Building Approach (7th ed.). John Wiley & Sons Ltd.Sekiguchi, T. (2011). Organisational Behavior & Human Decision Process (2nd ed.).Solimun. (2010). Analisis Multivariat Pemodelan Struktural. Metode PLS. CV Citra Malang.Srivastava, S. (2013). Job Satisfaction and Organisational Commitment Relationship : Effect of Personality Variables. Vision-The Journal of Business Perspective.Stephen P. Robbins, T. A. (2013). Organizational Behavior (15th ed.). New Jersey: Pearson.Sugiyono, P. D. (2014). Statistika Untuk Penelitian. Alfabeta.Suryani, R. E. (2019). Job Satisfaction and Citizenship Behavior of Employees of Private Universities in the Central Jakarta Region. International Review of Management and Marketing.Tabatabei, D. S. (2015). The Effective of Job Satisfaction on Organizational Citizenship Behavior. International Journal of Academic Research in Business and Social Sciences, Vol.5 No.1.Uma Sekaran, R. B. (2013). Research Method for Business: A Skill Building Approach (7th ed.). John Wiley & Sons Ltd.W Abdillah, J. H. (2015). Partial Least Square (PLS) : Alternatif Structural Equation Modelling (SEM) dalam Penelitian Bisnis. Yogyakarta: Penerbit Andi.Â